Evaluación de los cambios esqueléticos y dentales producidos con el tratamiento con placas de acetato y elásticos de clase III en pacientes con mesio-relación esquelética y dental en dentición primaria o mixta temprana - Espinal-B., Gabriel; Betancourt-P., John Jairo; Carrillo-P., Natalia; Piedrahíta-G., Maria Teresa (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Several authors have suggested the early treatment of oclusal alterations looking forward to change craniofacial growth conditions and diminish their expression with different appliances, one of them proposed by Franchi and Baccetti in 1998 for cases of mesiorrelations, which consists in bimaxilar resin splints with smooth oclusal planes and class III intermaxillary elastics. The present study pretended to evaluate the cephalometric and clinic changes with this therapy in 9 patients 4 and 7 years old with skeletal mesiorrelation during one year of treatment. Cephalic X-rays and dental casts were taken to each patient before starting the treatment at six months and one year later. The results show skeletal and dentoalveolar changes in the maxilla and the mandible. On the vertical plane it is suggested that a sagittal dysplasia compensation occurs and the changes in the soft tissues suggested the enhancement of facial aesthetics. It can be concluded that the therapy works positively in the mesio – relation in the children studied.